Distribution and assessment of heavy metal contents in surface sediments of the western Sunda Shelf. (July 2021) - Zhang, Hui; Liu, Shengfa; Wu, Kaikai; Cui, Jingjing; Zhu, Aimei; Zhang, Ying; Mohamed, Che Abd Rahim; Shi, Xuefa
Abstract: The heavy metal contents (Cr, Cu, Zn, Cd, Pb, Hg, and As) of 88 surface sediment samples from the western Sunda Shelf were analyzed to determine their spatial distribution patterns and contamination status. The results demonstrated that high enrichment regions of heavy metals were focused in the Kelantan, Pahang, and Ambat river estuaries, and deep water regions of the study area. These high enrichment regions were mainly controlled by riverine inputs and their hydrodynamic conditions. The enrichment factor ( EF ), geoaccumulation index ( I geo ), and potential ecological risk index ( PERI ) were used to assess heavy metal accumulation. The results indicated that the study area was not significantly contaminated overall at the time of the study; however, Cd, As, and Hg were at levels corresponding to moderate contamination at many stations located in the Pahang River estuary, Kelantan River estuary, and north-eastern region of the study area, primarily because of anthropogenic activities. Highlights: The heavy metal contents of surface sediment samples from the western Sunda Shelf were analyzed. High heavy metal enrichment regions were mainly controlled by riverine inputs and hydrodynamic conditions. The western Sunda Shelf was not significantly contaminated overall at the time of the study.